Influence of stiffener on aluminium perforated plates subjected to in-plane shear loading - Hassan, Mohd Nizam (2018)
Shear buckling is an important phenomenon as it enables the design becomes more efficient structures which would be possible if the critical buckling load is treated as the maximum allowable load. This is particularly significant in aerospace industry where lightweight, strength and reliability structures are known as the important factors need to be considered when designing and producing the aircraft. A literature review reveals that although there were many information available regarding to the buckling strength of elastic plates, but there is just few information available concerning the effect of shear buckling on the perforated plate. Therefore, the aim of this research was to study the effect of stiffener on aluminium perforated plates when subjected to shear loading. The research was conducted by using numerical method or known as finite element simulation software which was ABAQUS/CAE 6.10, since this tool were known as the most suitable technique for solving the problems. Aluminium 7075-T6 was the materials which have been selected and used throughout the study. Besides, the geometry of the model which was chosen for this study was square plate and rectangular plate. Before proceed to the main study, the mesh convergence analysis of non-perforated square plates and non-perforated rectangular plates were conducted to verify the method implemented in the research were correct and acceptable. The value of shear buckling coefficient then was validated by comparing the numerical data gained from the analysis with the theoretical data obtained from the literature study. After that, the shear buckling behaviors of perforated plates were studied by varying the diameter of holes and the quantity of holes on the plate structures. Further study was conducted into the buckling performance of perforated plates with stiffener under shear load. Based on the study, it was found that the design of perforation on the plate structures reduced the strength of that plate structures. However, when the stiffeners was added around the circular hole on the plates regions, it was noted that generally by the presence of the stiffeners improves the strength structure of the plates when compared with perforated plates. Finally, a full study of all design was finally undertaken which emphasizing the addition of stiffener have an effect on the buckling performance of the structure. The research was concludes with evaluations of the analysis and suggestions for future study direction.